+0

0
43
1

Assuming x doesn't equal -5 simplify (2x+10)^7/(x+5)^6

Guest Oct 4, 2017

#1
+4711
+1

$$\frac{(2x+10)^7}{(x+5)^6}$$

Factor a  2  out of  (2x + 10)  to get   2(x + 5) .

$$=\,\frac{(\,2(x+5)\,)^7}{(x+5)^6}$$

Remember that, for example,  (ab)3  =  ab * ab * ab  =  aaa * bbb  =  a3b3

$$=\,\frac{2^7(x+5)^7}{(x+5)^6}$$

Reduce the fraction by  (x + 5)6 .

$$=\,\frac{2^7(x+5)}{1} \\~\\ =\,128(x+5) \\~\\=\,128x+640$$

hectictar  Oct 4, 2017
Sort:

#1
+4711
+1

$$\frac{(2x+10)^7}{(x+5)^6}$$

Factor a  2  out of  (2x + 10)  to get   2(x + 5) .

$$=\,\frac{(\,2(x+5)\,)^7}{(x+5)^6}$$

Remember that, for example,  (ab)3  =  ab * ab * ab  =  aaa * bbb  =  a3b3

$$=\,\frac{2^7(x+5)^7}{(x+5)^6}$$

Reduce the fraction by  (x + 5)6 .

$$=\,\frac{2^7(x+5)}{1} \\~\\ =\,128(x+5) \\~\\=\,128x+640$$

hectictar  Oct 4, 2017

### 24 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details